2017
DOI: 10.1002/adhm.201700660
|View full text |Cite
|
Sign up to set email alerts
|

Periosteum Extracellular‐Matrix‐Mediated Acellular Mineralization during Bone Formation

Abstract: Cell-mediated mineralization is essential for bone formation and regeneration. In this study, it is proven that extracellular matrix (ECM) of decellularized periosteum can play an initiative and independent role in bone-like apatite formation. Using decellularized periosteum scaffold, it is revealed that ECM scaffold itself can promote critical bone defect regeneration and nude mouse ectopic ossification. The natural collagen matrix of decellularized periosteum can serve as a 3D structural template for Ca-P nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Higher levels of mineralized tissue and increased vascular volume were observed 8 weeks after implantation, which might be caused by reduced production of IL-1b and IL-8 and superior osteogenic capacity compared to native GP (Cunniffe et al, 2017). In addition, 3D ECM scaffold produced from decellularized periosteum promoted bone mineralization by controlling the size and direction of mineral crystals in rabbit bone defect regeneration, suggesting the crucial role of periosteum ECM in efficient healing of fractures and bone regeneration (Lin et al, 2018). In clinical, decellularized bone ECM from bovine trabecular bone discs with patient autogenous MSCs could treat distal tibia fracture.…”
Section: Tissue-derived Decellularized Ecm Scaffoldmentioning
confidence: 96%
“…Higher levels of mineralized tissue and increased vascular volume were observed 8 weeks after implantation, which might be caused by reduced production of IL-1b and IL-8 and superior osteogenic capacity compared to native GP (Cunniffe et al, 2017). In addition, 3D ECM scaffold produced from decellularized periosteum promoted bone mineralization by controlling the size and direction of mineral crystals in rabbit bone defect regeneration, suggesting the crucial role of periosteum ECM in efficient healing of fractures and bone regeneration (Lin et al, 2018). In clinical, decellularized bone ECM from bovine trabecular bone discs with patient autogenous MSCs could treat distal tibia fracture.…”
Section: Tissue-derived Decellularized Ecm Scaffoldmentioning
confidence: 96%
“…Increasing evidence showed that ECM-based TEB was capable of delivering biological signals, such as cell adhesion sites, which is analogous to bone regeneration microenvironments and a new strategy for tissue repair. 2326 Previous studies conducted by our group have found that MSC ECM-based TEBs released a variety of active proteins with osteogenesis activity and increased osteoinductivity. In the present study, we demonstrated that MSC/POC ECM-based TEBs significantly enhanced osteogenesis in a rat femur defect model compared with MSC ECM-based TEBs.…”
Section: Discussionmentioning
confidence: 98%
“…Decellularized ECM derived from porcine periosteum has been shown to promote mineral deposition and orthotopic bone formation in rabbits. [290] Additionally, when administered in the form of a hydrogel, decellularized periosteal ECM can promote M2 macrophage polarization, angiogenesis, and mature bone formation in rat critical-sized calvarial defects. [291] However, when implanted into a calvarial defect, the decellularized periosteal ECM hydrogel is subject to relatively rapid degradation (<7 days).…”
Section: Decellularized Ecmmentioning
confidence: 99%
“…Due to the critical role of periosteum in the bone repair process, a number of research groups have attempted to utilize decellularized periosteal ECM for inducing the repair of bone defects. Decellularized ECM derived from porcine periosteum has been shown to promote mineral deposition and orthotopic bone formation in rabbits 290. Additionally, when administered in the form of a hydrogel, decellularized periosteal ECM can promote M2 macrophage polarization, angiogenesis, and mature bone formation in rat critical‐sized calvarial defects 291.…”
Section: Strategies To Improve Biomaterials For Bone Regenerationmentioning
confidence: 99%